Sustainability Performance Approach in Malaysia’s SMEs for Improving Green Supply Chain Management (GSCM); An Application of Quality Function Deployment (QFD) - Mohd Rozar, Norlinda; Razik, Muhammad Ashlyzan; Zakaria, Mohd Nazri (ExcelingTech, 2019)
Many perceptions from environmental studies were claimed that environmental pollution in Malaysia is due to the failure of Green Supply Chain Management (GSCM) among Small Medium Enterprise (SMEs). There is a need to see an effective strategy to overcome the GSCM failures or to improve the GSCM in SMEs. Since,